Análise da dinâmica fluvial Rio Paraguai entre foz do Córrego Chafariz e a foz do Rio Cachoeirinha-MT - Chaves, Istéria Jovem de Freitas (2015)
The remarkable rainfall seasons cause the extreme flow in the drainage systems of Mato Grosso State as a whole, and in the Paraguay River this condition is not different. A sector of this river, between the mouth of the Chafariz creek and Cachoeirinha creek, was chosen for the study on the fluvial dynamics and its relation to land use. The work was supported by literature review, acquisition and processing of Landsat 5 satellite images for making the maps of land use and fluvial dynamics, survey of bathymetric data in the field, collection of bottom sediments, water collection for analysis of sediments in suspension and measurements of turbidity. Analyzes were performed according to the procedures described in literature. The information for the production of the maps was obtained by supervised visual image interpretation. In terms of land use, in the period considered in this work (1986 and 2010), there was a decrease of the Savannah (Brazilian Cerrado) area and an increase of the pasture area. On the bottom sediments, particle size ranged from thick pebbles to clay. The sediments in suspension showed the same value (40 mg/L) in all monitored sections during the dry season of 2013, except in section V which decreased by 25%. The amount of sediments in suspension in the flood period doubled in almost all sections. The highest recorded water flow, in both dry (200 m3/s) and flood (640 m3/s) seasons, was obtained in Section V, a meandering sector with ablation and deposition margins marked by the forms of sidebars, levees, islands, secondary channels, ponds, oxbow lakes and bays. Numerous water bodies, typical of rivers in flatland and wetland (Brazilian Pantanal), mark the floodplain.